2020
DOI: 10.1111/srt.12851
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing rosacea from sensitive skin by reflectance confocal microscopy

Abstract: Background: The updated standard classification and pathophysiology of rosacea have provided clear and meaningful evaluation parameters; however, differentiating rosacea from sensitive skin (SS) remained an obstacle for dermatologists around the world, especially in China. Herein, we aimed to find a better characteristic to distinguish rosacea from SS by using reflectance confocal microscopy (RCM). Method: Forty rosacea patients and 143 healthy subjects were recruited in this study. Firstly, a SS questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“… 60 Three studies focused on using the structure of epidermal lesions determined by RCM to assess sensitive skin. 37 , 61 , 62 Notably, SS and NSS subjects differed in honeycomb structure depth or structure. In one study, the honeycomb structure was shallower in SS than in NSS subjects, 61 while in the other two studies, patients with lactic acid stingers had irregular honeycomb structures on the face.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“… 60 Three studies focused on using the structure of epidermal lesions determined by RCM to assess sensitive skin. 37 , 61 , 62 Notably, SS and NSS subjects differed in honeycomb structure depth or structure. In one study, the honeycomb structure was shallower in SS than in NSS subjects, 61 while in the other two studies, patients with lactic acid stingers had irregular honeycomb structures on the face.…”
Section: Resultsmentioning
confidence: 92%
“…In one study, the honeycomb structure was shallower in SS than in NSS subjects, 61 while in the other two studies, patients with lactic acid stingers had irregular honeycomb structures on the face. 37 , 62 …”
Section: Resultsmentioning
confidence: 99%
“…While sensitive skin was first shown to be the same entity as or a subgroup of rosacea in a previous study (30), it can now be distinguished from rosacea through diagnostic methods (e.g., reflectance confocal microscopy) (30). In our study, sensitive skin was frequently observed in the patients with rosacea, but the prevalence rates of allergic contact and photocontact dermatitis were also high in the patients with sensitive skin, probably due to the use of makeup and skin care products or skin care habits (31).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies demonstrated that the prevalence of sensitive skin symptoms is higher in subjects with rosacea, 22 while LAST and CAT are commonly used to determine whether individuals have sensitive skin. 23,24 In agreement with previous studies, 25,26 we demonstrated here that the positive rates of both LAST and CAT were significantly higher in subjects with rosacea than in normal controls.…”
Section: Discussionmentioning
confidence: 99%